2019
DOI: 10.4028/www.scientific.net/kem.809.140
|View full text |Cite
|
Sign up to set email alerts
|

Injection Moulding of Oxide Ceramic Matrix Composites: Comparing Two Feedstocks

Abstract: Ceramic materials are suitable for use in the high temperature range. Oxide ceramics, in particular, have a high potential for long-term applications under thermal cycling and oxidising atmosphere. However, monolithic oxide ceramics are unsuitable for use in high-temperature technical applications because of their brittleness. Thin-walled, oxidation resistant, and high-temperature resistant materials can be developed by reinforcing oxide ceramics with ceramic fibres such as alumina fibres. The increase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…1,2 These reinforcements are mainly used as continuous fibers, in the form of woven fabrics, [2][3][4][5][6][7][8][9][10][11][12] Honoring Dr. Mrityunjay Singh unidirectional (UD) layers, [13][14][15] or braiding. 4,16 However, only few studies [17][18][19][20][21][22] dealt with Nextel™ 610 short fiber-reinforced oxide ceramics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 These reinforcements are mainly used as continuous fibers, in the form of woven fabrics, [2][3][4][5][6][7][8][9][10][11][12] Honoring Dr. Mrityunjay Singh unidirectional (UD) layers, [13][14][15] or braiding. 4,16 However, only few studies [17][18][19][20][21][22] dealt with Nextel™ 610 short fiber-reinforced oxide ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…25 Short fiber-reinforced OFCs can be produced automatically via ceramic injection molding or a fiber spraying process. Currently, there are two [17][18][19][20] known research activities on ceramic injection molding of complex nearnet-shape OFC components. Previous studies reported that during the injection molding process (kneading, extrusion, and injection), Nextel™ 610 fiber bundles were broken, separated into single fibers, and oriented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the brittleness of oxide ceramic materials is the issue. Therefore, fibre-reinforced oxide ceramics (OCMC) are gaining great of attention compared to monolithic oxide ceramics owing to their higher fracture toughness and damage tolerance under thermal and mechanical load [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several progresses are driven toward the enhancement of these properties using several type of reinforcements. In fact, two types of fiber reinforcements were frequently used in the literature [3]. Oxide fibers such as alumina fiber were incorporated within oxide ceramics as they offer excellent oxidation resistance and good mechanical properties but creep faster at high temperature comparing to non-oxide fibers.…”
Section: Introductionmentioning
confidence: 99%